Ecosistemi formativi inclusivi - GIACONI, Catia; D'Angelo, Ilaria; Marfoglia, Alessandra; Gentilozzi, Chiara (Traiettorie inclusive, 2023)
The volume titled ""Inclusive Educational Ecosystems"" presents a collection of new experiences and synergies focused on the theme of inclusion within several educational contexts. Through the insightful contributions of diverse authors, this book addresses the challenges and aspirations of creating generative spaces that connect universities, schools, and territories. Comprised of two thought-provoking sections, ""Generative Challenges between Universities and Schools"" and ""Generative Challenges between Universities and Territories,"" this collective work delves into current issues necessitating transversal and systemic actions. Gain insights and evidence-based solutions as you explore the pages of this volume.